Impact of environmental and climate conditions on the investment potential of real estate in the belt of the Gulf of Gdansk Coast - Jasińska Elżbieta (E3S Web of Conferences, 2019)
The subject of this publication is to determine what environmental and climatic factors can significantly affect the value of real estate. As a research object, there was chosen area surrounding the Gulf of Gdansk, which, like the entire coast, is attractive for investment and constitutes an interesting object as a space with a special focus on tourism, including short-term rental. Progressing climate change is particularly affecting this sector. It is safe to assume that unfavorable environmental conditions can significantly change the attractiveness of this area. Therefore, the research hypothesis about the correlation between climate aspects distinguishing the coastal belt and the distribution of real estate prices in the selected area has been verified. The area of the Gulf of Gdansk Coast and the technical and protective belt were analyzed. The weather situation on the coast is different from that prevailing in the rest of the country. There are strong and gusty winds, local floods, but at the same time a natural landscape, proximity to the sea and clean, iodized air. Other possible climatic factors have also been tracked, i.e. temperature, sea level and possible changes that may occur over the next years. The analyzes were based on the data of the KLIMAT project entitled "The impact of climate change on the environment, economy and society", and the Government Project KLIMADA and SPA analyzes. An in-depth analysis of the problem of combining planning documents for the maritime sector influencing the Study of Spatial Development of Polish Marine Areas with Local Spatial Management Plans, introduced Flood Risk Maps and Flood Risk Maps was also conducted.